“Case Method” in the teaching of disciplines in Basic Medical Sciences in IIUM - Myint, Yi Yi; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; Syed Ahmad, Pakeer Oothuman (2013)

(untitled)
Background: Case method (CM) as a teaching methodology to promote active learning and the professional development of students has been successfully employed in a number of fields other than medicine. In the Medical Programme of International Islamic University Malaysia (IIUM) we examined the application of CM in the teaching of disciplines in various basic medical sciences by integrating knowledge in these disciplines into the clinical sciences in a large group of students. Methods:This study involved Phase I preclinical medical students (Years 1and 2) of the academic session 2011/2012. Thirteen CM modules were implemented. A cotent-expert facilitator led a two-hour session for each of the modules which involveda class of about 130 students. Following such an implementation,the perception of students towards CM was studied through a self-administered 19 item-questionnairewith a response scale of 4. Results:About 81% (215/265) of students participated in the questionnaire. More than 90% of these students agreed that CM sessions made efficient use of time,prior to and during the CM session. The structure promoted learning and helped develop problem solving skills. CM sessionsalso provided opportunities to explore related topics, to make use of the knowledge gained in solving other cases,for tutor participation and feedback. The mean scores for all the 19 items except for two were significantly higher in theYear 1 students than that of the Year 2 students (p<0.05).About 80% of Year 1 students and 60% of Year 2 students preferred to have both Problem-based Learning and CM incorporated into the medical curriculum of IIUM. Conclusion:CM has a potential role in the teaching of the applied aspects of disciplines of basic medical sciences. Keywords: Case Method, Basic Medical Science, Medical Students